Dimensi Iklim Keselamatan dan Perbandingan Variabel di PT. XYZ Tahun 2021 - Novriza, Venti; Lestari, Fatma (UI Scholars Hub, 2021)
In the current situation, where the Indonesian government prioritizes high-rise buildings and infrastructure, cement is impacted, and concrete demand is high—event on this pandemic situation PT XYZ as an essential company its’ can continue to business operation. PT XZY commits to safety and health. The study aims to explore the dimension of safety climate and compare variables. The cross-sectional method used by the DK3N questioner was used by previous Safety Climate research. Tabulated data univariate method used by SPSS 25. Result respondent demography by gender 92 % male, 8% female, by age < 40 years 80%, > 40 years 20%, by position officer 21%, management 79%. Overall, XYZ's safety climate is good with a mean of 4.15 of 0-6 scale, with the positive element being: Safety Training, Management Commitment. The result comparison variable by position is higher management (4.07) than an officer (3.95).